A celebração da Palavra de Deus à luz do Vaticano II: elementos restaurados, fonte de fé e mistério pascal de Cristo - Massaro, André Luiz (2017)
The purpose of the present work was to reflect on the celebration of the Word of God restored by the Second Vatican Council, pointing out its various celebratory modalities that can be celebrated by families as a source of supply and growth in the Christian faith, based on knowledge and appreciation of elements rescued with the liturgical reform of Vatican II and that are explicit in the Constitution Sacrosanctum Concilium. In this sense, an attempt was made to make a historical rescue on all the work of the conciliar priests of Vatican II, who took the liturgy of the Church to a movement of return to its biblical and patristic sources. Thus, through applied research, it is noted that the Celebration of the Word of God does not exist to heal the lack of ordained ministers and / or in turn to replace the difficulty of the Celebration of the Eucharist. It has its own peculiar characteristics and can lead the baptized to a deeper degree of evangelization. From the theological method of seeing, judging and acting, we sought to demonstrate the full range of elements extolling the liturgy of the Word of God celebrated by the communities in chapels, churches, balconies, factories, houses and in the most improvised places imaginable, but which must be celebrated in an active, full and conscious way, achieving fruitful participation in life. The proposal is provocative and in order to achieve its objectives requires study, knowledge and fidelity to the Sacred Liturgy of the Church, enabling the lay protagonism; a coalition with a temptation of Church-clericalism; leading the laity to live their vocation of salt of the earth and light in the world on the frontiers of mission: a Samaritan and outgoing Church